2020
DOI: 10.1093/mnras/staa401
|View full text |Cite
|
Sign up to set email alerts
|

A detailed study on the reflection component for the black hole candidate MAXI J1836−194

Abstract: We present a detailed spectral analysis of the black hole candidate MAXI J1836-194. The source was caught in the intermediate state during its 2011 outburst by Suzaku and RXTE. We jointly fit the X-ray data from these two missions using the relxill model to study the reflection component, and a steep inner emissivity profile indicating a compact corona as the primary source is required in order to achieve a good fit. In addition, a reflection model with a lamp-post configuration (relxilllp), which is normally … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 65 publications
6
9
0
Order By: Relevance
“…We stress that the goal of these phenomenological spectral fits is simply to constrain the location of the X-ray emitting region by quantifying the presence or absences of reflection features. These phenomenological spectral fits favour the inverse Compton scenario, as the reflection features are very strong, particularly near the peak of the outburst, in agreement with other works (Reis et al 2012, Dong et al 2020). This picture is further strengthened by our tentative detection of a hard lag in the X-ray lightcurves.…”
Section: X-ray Spectral Fitssupporting
confidence: 90%
See 1 more Smart Citation
“…We stress that the goal of these phenomenological spectral fits is simply to constrain the location of the X-ray emitting region by quantifying the presence or absences of reflection features. These phenomenological spectral fits favour the inverse Compton scenario, as the reflection features are very strong, particularly near the peak of the outburst, in agreement with other works (Reis et al 2012, Dong et al 2020). This picture is further strengthened by our tentative detection of a hard lag in the X-ray lightcurves.…”
Section: X-ray Spectral Fitssupporting
confidence: 90%
“…MAXI J1836−194 is a low mass BHXB that went in outburst during late August 2011; it was quickly identified as a black hole candidate (Negoro et al 2011, Strohmayer & Smith 2011, Miller-Jones et al 2011, Russell et al 2011. Later studies of the source's X-ray spectra found that the black hole spin is likely high (≈ 0.9), and that the hard X-rays show a very prominent reflection component (Reis et al 2012, Dong et al 2020. Rather than undergoing a full outburst, the source reached a hard-intermediate state (HIMS) before going back into the HS and fading into quiescence (Ferrigno et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Supersolar abundances have been inferred from K lines of different elements observed in the X-ray spectra of X-ray binaries (XRB) and active galactic nuclei (AGN) (see e.g., Kallman et al (2009); Dong et al (2020); Walton et al (2020); Fukumura et al (2021)). These absorption and emission features can occur in the inner regions of the black-hole accretion disks where the plasma densities are predicted to range from 10 15 to 10 22 cm −3 (Schnittman et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Supersolar abundances have been inferred from K lines of different elements observed in the X-ray spectra of X-ray binaries (XRB) and active galactic nuclei (AGN) (see e.g., Kallman et al (2009); Dong et al (2020); Walton et al (2020); Fukumura et al (2021)). These absorption and emission features can occur in the inner regions of the black-hole accretion disks where the plasma densities are predicted to range from 10 15 to 10 22 cm −3 (Schnittman et al 2013).…”
Section: Introductionmentioning
confidence: 99%